CONJUCTIONLESS SEQUENCES OF SUCCESSIVE ACTIONS AS MEANS OF EXPRESSION OF SEMELFACTIVITY OF AN ACTION IN GERMAN - Smerechynska , Oksana (Philological Treatises, 2020)
The aspectological context of sequences of successive actions is considered to be very important for expressing actional meaning of boundedness of an action in German. The sequences of successive actions are characterized by the meanings of temporal contact and semelfactivity of the corresponding actions as well as their correlation with a definite moment of time. The aim of the paper is to investigate the influence of conjuctionless sequences of successive actions on the expression of semantics of an bounded semelfactive action with the help of nonbounded or just potentially bounded verbs. There are identified lexical-semantical groups of verbs that can express the meaning of the bounded semelfactive action in the respective context as well as the frequency of using of sequences of successive actions as the main means of expression for expressing the bounded semantics of semelfactivity of an action in the analyzed works in German. In the paper the sequences of successive actions are analyzed that are realized in the multi-component sentences with one subject, in the conjuctionless multi-component sentences with different subjects and in the syntactical structures where we can distinguish between adjacent sentences that may be parts of different paragraphs and reactions to direct speech. Based on the obtained data we consider the sequences of successive actions to be situated near the near-core zone of the functional-semantic microfield of semelfactivity of an action in German.